Factors Affecting the Independence of the Primipara Mother in Care of the Infant at Pidie Jaya Hospital - Putri Zahara; Ismail Efendi; Yuniati Yuniati (Newinera Publisher, 2022)
The research objective to be achieved is to analyze the factors that influence the independence of primiparous mothers in caring for babies in Pidie Jaya Hospital. This type of research uses a descriptive analytic survey with a cross sectional design. The population in this study amounted to 56 people, while the sample amounted to 56 Primiparous mothers, with total sampling technique. Data analysis was carried out by univariate, bivariate and multivariate analysis. Based on the results of the chi-square test, it is known that the independence of primiparous mothers is related to maternal knowledge p = 0.000, culture = 0.002, trust p = 0.001, maternal age p = 0.001, family support p = 0.003 means that there is a relationship between mother's knowledge, culture, and beliefs. Maternal age, and family support with primiparous mother independence. From the results of multivariate analysis, it is known that the most dominant variable influencing in this study is the Mother's Knowledge variable with an OR value of 21,483. The conclusion in this study is that there is an influence of mother's knowledge, culture, beliefs, maternal age and family support and the most influential variable is mother's knowledge. The suggestion is that it is hoped that this research can be used as reference material for hospitals, especially increasing the competence of midwives in order to maximize mother's knowledge during hospitalization so that they can independently care for their babies at home.